(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The global food enterprise faces escalating pressure to set up and hold obvious deliver chains to make certain the safety and authenticity of meals merchandise. This research paper delves into the transformative potential of blockchain era in addressing these important troubles. Blockchain, characterised by its decentralized, tamperresistant nature, emerges as a promising answer for enhancing transparency in the course of the food supply chain. Through an exhaustive assessment of existing literature and an evaluation of a hit case studies, this paper targets to elucidate the position of blockchain in revolutionizing the food industry. The literature review gives a comprehensive evaluation of blockchain generation, highlighting its essential features along with decentralization, immutability, and transparency. Subsequently, an exploration of existing research on blockchain inside the food industry offers insights into successful implementations and classes discovered. The method segment outlines the studies layout, incorporating a systematic literature evaluation and case examine analysis to derive significant conclusions. The middle contribution of this paper lies inside the proposed Blockchain Implementation Framework. This framework introduces design ideas that emphasize scalability, interoperability, and person accessibility. It underscores the essential position of stakeholder engagement, advocating collaboration amongst numerous actors in the food deliver chain. The technical infrastructure segment outlines the important thing requirements for a blockchain-primarily based obvious meals deliver chain, addressing issues for platform selection and clever agreement improvement. Furthermore, the framework navigates the complex regulatory panorama, imparting techniques for ensuring compliance with industry requirements. To validate the framework, the paper includes a case observe analysis providing successful implementations of blockchain in meals supply chains. These case research offer valuable insights into the effect of blockchain on transparency, traceability, and average supply chain efficiency. While highlighting the promising prospects of blockchain technology, the paper additionally acknowledges and addresses challenges related to implementation. The end synthesizes key findings, providing hints for enterprise stakeholders and suggesting destiny studies instructions. This study contributes to the continuing discourse on leveraging blockchain for transparent meals deliver chains, fostering a safer and more straightforward worldwide food atmosphere.